Leading with compassion in health care organisations: The development of a compassion recognition scheme-evaluation and analysis. Issue 2 (27th March 2018) - Hewison, Alistair; Sawbridge, Yvonne; Cragg, Robert; Rogers, Laura; Lehmann, Sarah; Rook, Jane
Abstract : Purpose: The purpose of this paper is to report an evaluation of a leading-with-compassion recognition scheme and to present a new framework for compassion derived from the data. Design/methodology/approach: Qualitative semi-structured interviews, a focus group and thematic data analysis. Content analysis of 1, 500 nominations of compassionate acts. Findings: The scheme highlighted that compassion towards staff and patients was important. Links to the wider well-being strategies of some of the ten organisations involved were unclear. Awareness of the scheme varied and it was introduced in different ways. Tensions included the extent to which compassion should be expected as part of normal practice and whether recognition was required, association of the scheme with the term leadership, and the risk of portraying compassion as something separate, rather than an integral part of the culture. A novel model of compassion was developed from the analysis of 1, 500 nominations. Research limitations/implications: The number of respondents in the evaluation phase was relatively low. The model of compassion contributes to the developing knowledge base in this area. Practical implications: The model of compassion can be used to demonstrate what compassion "looks like", and what is expected of staff to work compassionately. Originality/value: A unique model of compassion derived directly from descriptions of compassionate acts which identifies the impact of compassion on staff.